2005
DOI: 10.1002/jmri.20233
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of in vivo kinematics after total knee arthroplasty

Abstract: Purpose:To improve the quality of magnetic resonance imaging (MRI) on knees after total knee arthroplasty (TKA) by minimizing image artifacts caused by metallic implants, and to establish a method determining in vivo kinematics of TKA knees using MRI. Materials and Methods:Two knee implants made of cobaltchrome and oxidized zirconium were tested with different pulse sequences and imaging parameters. Then, in vivo kinematic MRI was performed on five well-functioning TKAs under simulated weight-bearing condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Another technique recently applied have been highfield MRI (Lee et al, 2005;Sheehan et al, 1999). However, due to the construction of the MR scanner, the assessment can only be performed in knee flexion angles of less than 601, although it has been demonstrated that after TKA significant alterations in patellar kinematics occur especially in greater flexion angles (Tanzer et al, 2001).…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…Another technique recently applied have been highfield MRI (Lee et al, 2005;Sheehan et al, 1999). However, due to the construction of the MR scanner, the assessment can only be performed in knee flexion angles of less than 601, although it has been demonstrated that after TKA significant alterations in patellar kinematics occur especially in greater flexion angles (Tanzer et al, 2001).…”
Section: Article In Pressmentioning
confidence: 99%
“…Due to the 2D nature of fluoroscopy, motions perpendicular to the fluoroscopic images are difficult to evaluate reliable. Therefore the femoro-patellar 3D kinematics and its relationship to changes in femoro-tibial motion patterns remained less clear (Lee et al, 2005). However, patello-femoral disorders due to changes of the patellar kinematics are responsible for up to 50% of all revisions after total knee replacement Lee et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo studies have been conducted on the replaced joint, using MRI [33,34] and fluoroscopy [35,36], but none of them has looked at changes due to arthroplasty, and only sagittal-plane patellar kinematics are available when using fluoroscopy. There is, therefore, a lack of in vivo data regarding intraoperative patellar kinematics and the changes caused by arthroplasty.…”
Section: Introductionmentioning
confidence: 99%
“…Maltracking may result from excessive or unbalanced tension in the surrounding soft tissues during knee flexion, so our radiographic measurements do not reflect patello-femoral congruence during ROM. A CT scan or MRI in vivo assessment might be necessary [18,40,41]. Anyway, Varadarajan et al [42] demonstrated that, even with a correct external rotation, the trochlear groove in current TKA designs only partially restores normal anatomy.…”
Section: Discussionmentioning
confidence: 97%